Knee MRI patterns of bone marrow reconversion and relationship to anemia. (August 2016) - Gonzalez, Felix M; Mitchell, Jason; Monfred, Erica; Anguh, Terence; Mulligan, Michael
Background: Bone marrow changes are commonly encountered on knee magnetic resonance imaging (MRI). The clinical relevance of these changes, especially as they relate to anemia, has not been studied in a large patient series. Purpose: To determine if the extent of bone marrow reconversion (BMR) can assist the radiologist in making recommendations for further evaluation for underlying anemia. Material and Methods: This study included 457 patients who had knee MRI over a 2-year period. Bone marrow patterns in the distal femur, proximal tibia, and fibula were graded as follows: 1, homogeneous fatty marrow; 2, patchy red marrow in the distal femur; 3, patchy red marrow in the distal femur and tibia and/or fibula; and 4, complete BMR in the femoral, tibial, and/or fibular metaphyses. Results: There was a statistically significant difference ( P  < 0.001) between the hemoglobin concentration and BMR grades. In women, anemia (Hb ≤12.0 g/dL) was found in 31 of 127 (24%) patients with grade 1, 31 of 83 (37%) with grade 2, 24 of 64 (37%) with grade 3, and 12 of 24 (50%) with grade 4. In men, anemia (Hb ≤13.0 g/dL) was found in 33 of 125 (26%) patients with grade 1, 12 of 19 (63%) with grade 2, five of 14 (36%) with grade 3, but not in the one patient with grade 4. Conclusion: Women demonstrating marrow changes of a grade 4 BMR pattern should get a laboratory assessment for anemia.